2010
DOI: 10.1007/s10964-010-9541-6
|View full text |Cite
|
Sign up to set email alerts
|

Active and Engaged Citizenship: Multi-group and Longitudinal Factorial Analysis of an Integrated Construct of Civic Engagement

Abstract: Civic participation does not necessarily equate to civic engagement. However, to date, integrated measures of civic engagement that go beyond civic behaviors have not been developed. In this article, we propose an integrated construct of civic engagement, active and engaged citizenship (AEC), that includes behavioral, cognitive, and socioemotional constructs. Using data from 909 adolescents (62.4% girls) who took part in the Grades 8-10 assessments of the longitudinal 4-H Study of Positive Youth Development (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 31 publications
4
121
1
5
Order By: Relevance
“…Lerner et al in press;Lerner 2009). In addition, research has identified the individual and ecological bases of the development of these characteristics and theoretically expected outcomes of the PYD process, e.g., youth community contribution or active and engaged citizenship (e.g., Zaff et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Lerner et al in press;Lerner 2009). In addition, research has identified the individual and ecological bases of the development of these characteristics and theoretically expected outcomes of the PYD process, e.g., youth community contribution or active and engaged citizenship (e.g., Zaff et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, civic engagement refers to civic action or activities [Hart et al, 2007;Obradović & Masten, 2007;Pancer, Pratt, Hunsberger, & Alisat, 2007;Stepick, Stepick, & Labissiere, 2008] directed toward one's community or society. Sometimes, civic engagement is measured through civic attitudes [Flanagan et al, 2007;Henderson, Brown, Pancer, & Ellis-Hale, 2007;Schmidt, Shumow, & Kackar, 2007], or in terms of intentions or goals for the future [Metz, McLellan, & Youniss, 2003], or includes skills and capacities [Flanagan & Faison, 2001;Zaff, Boyd, Li, Lerner, & Lerner, 2010]. Further, the concept of civic engagement is used to refer to community-oriented activities such as volunteerism or overtly political activities such as voting or campaigning [e.g., Adler & Goggin, 2005;Ekman & Amnå, 2012].…”
mentioning
confidence: 99%
“…Self-efficacy can be defined as an individuals' sense of control and agency over events in their lives (Bandura, 1997). Civic self-efficacy describes the belief that one's individual civic actions will lead to change (Shuler, 2010;Zaff, Boyd, Li, Lerner & Lerner, 2010). A number of studies have demonstrated a relationship between interactive civic experiences and increased civic self-efficacy (Astin, Vogelgesang, Ikeda & Yee, 2000;Barr, 2010;Moely, MacFarland, Miron, Mercer & Ilustre, 2002).…”
Section: Civic Self-efficacymentioning
confidence: 99%